The ideal kitchen - Secrest, Birdie (My University, 1892)
Introduction: The time is coming when skill in cooking and good kitchen management will not be regarded disdainfully; when to prepare a good meal and serve it well, with deft hand and womanly taste will be no more of a condescention than to write a poem or paint a picture. And oh, for the dawn of the coming when all woman-kind will see it as such; when every girl will regard the kitchen as something more than a dungeon to be shunned, in which Bridget was born to drudge; but wherein she brings a smiling face and finds pleasure in expending her energies over that which is well worth cultivation, in making herself one of that noble race of women for whom we patiently wait and whose coming we think is near. There are many who say with an air of indifference, that they have no talent for these things. But why not cultivate a talent in this direction, as well as in executive ability, capacity for management, or skill in selecting good servants? Does not the one precede the other? Why not make the kitchen what it ought to be, the pleasantest place in the house?
Citation: Secrest, Birdie. The ideal kitchen. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Home economics; Women; Kitchen; Theses; Manuscripts (documents)